2012
DOI: 10.3174/ajnr.a2887
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Focal Cerebral Ischemia Injury Model in Adult Mice: Assessment Using 7T MR Imaging

Abstract: BACKGROUND AND PURPOSE:A stable stroke experimental model is highly desirable for performing longitudinal studies using MR imaging. The purpose of this study is to establish a stable focal cerebral ischemia model with a high survival rate in adult mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Despite the fact the hippocampus, thalamus and amygdala are not supplied by the MCA, it is not uncommon for these regions to show evidence of ischemic injury following MCAO [ 19 , 44 , 45 , 59 ], for several reasons. First and foremost, C57BL/6 mice may be more susceptible to variation in intraluminal filament MCAO compared to other strains owing to a common lack of patency in posterior communicating arteries (PComA) [ 31 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact the hippocampus, thalamus and amygdala are not supplied by the MCA, it is not uncommon for these regions to show evidence of ischemic injury following MCAO [ 19 , 44 , 45 , 59 ], for several reasons. First and foremost, C57BL/6 mice may be more susceptible to variation in intraluminal filament MCAO compared to other strains owing to a common lack of patency in posterior communicating arteries (PComA) [ 31 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-seven [1]percent of all strokes in humans are ischemic and most frequently caused by cerebral thromboembolism [2–4]. Cerebral thrombosis or embolism leads to ischemic stroke with cerebral thrombosis being more common [5, 6]. Cerebral thrombosis is the formation of a blood clot at a congested cerebral vessel due to atherosclerosis of brain arteries, normally caused by an accumulation of fatty deposits inside the blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The CV of infarct volume in rodent experimental stroke models has a wide range between 0.05 to 2, depending on the model, choice of anesthetic and how well physiological and hemodynamic variables are controlled, among other factors (Liu et al, 2009). Similarly, Zhang F et al found that infarct location and size were highly variable in mouse stroke models, with the thromboembolic model showing highest variability in infarct size of 0.44 and lowest 7-day survival (Zhang et al, 2012). …”
Section: Discussionmentioning
confidence: 96%